2020
DOI: 10.1080/19361653.2020.1812465
|View full text |Cite
|
Sign up to set email alerts
|

Social support, discrimination, and Self-Esteem in LGBTQ + high school and Post-Secondary students

Abstract: LGBTQ+ (lesbian, gay, bisexual, transgender, queer, plus) people are at a disadvantage compared to their heterosexual and cisgender (non-transgender) counterparts. LGBTQ+ people are likely to be discriminated against based on their gender or sexual identities. Drawing on data from the OutLook Study in Waterloo Region, Ontario, Canada, this paper examines discrimination and social support among high school and post-secondary students, and how they are related to self-esteem. Using t-tests, we found that transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another sub-theme was the experience of low self-esteem among individuals identifying as LGBTI+. Most of the participants in the current study underlined that their self-esteem was dented by issues of homophobia and transphobia which is evident in other studies also (Taylor et al 2019 :19). There is however, contrasting findings as a study in Brazil found that high rates of self-esteem in a majority of the participants (Canali et al 2014 :4509).…”
Section: Discussionsupporting
confidence: 71%
“…Another sub-theme was the experience of low self-esteem among individuals identifying as LGBTI+. Most of the participants in the current study underlined that their self-esteem was dented by issues of homophobia and transphobia which is evident in other studies also (Taylor et al 2019 :19). There is however, contrasting findings as a study in Brazil found that high rates of self-esteem in a majority of the participants (Canali et al 2014 :4509).…”
Section: Discussionsupporting
confidence: 71%
“…In Hendricks and Testa’s (2012) adaptation of this model for gender minority populations, they noted that among the few studies focused on transgender resilience, social support is identified as a source of strength. However, transgender youth and adults often report having less social support than their cisgender counterparts (Alanko & Lund, 2020; Aparicio-García et al, 2018; Davey et al, 2014), especially familial social support (Factor & Rothblum, 2007; Taylor et al, 2022).…”
Section: A Note About Languagementioning
confidence: 99%
“…Studies show that having supportive peers to discuss problems increased the risks of suicidal ideation and attempts for LGBTQ youth, particularly for LGBQ youth who have had been victimized and gender minority youth [17,96]. Generally, social support did not buffer effects of victimization on self-esteem for LGBTQ students [108], questioning the nuances in the efficacy of peer support as a social support system. and school staff were ineffective and inconsistent in supporting LGBTQ students (n articles = 7), and (4) school staff perceived external support as key to ensure coordination of inclusivity for LGBTQ students (n articles = 4).…”
Section: Inconsistencies In the Effectiveness Of Peer Support For Div...mentioning
confidence: 99%